Multijet impingement heat transfer under the combined effects of encapsulated-PCM and inclined magnetic field during nanoliquid convection - Selimefendigil, Fatih; Öztop, Hakan Fehmi (Pergamon-Elsevier Science Ltd, 2023)
In this study, convective heat transfer performance for confined multiple jet impinging system with phase change-packed bed (PCM-PB) installed sub-system under magnetic field effects is numerically assessed during hybrid nanoliquid convection. Both phase transition and heat transfer dynamics are analyzed by using finite element method. Numerical study is conducted for different magnetic field strength (Hart-mann number-Ha between 0-40), inclination (between 0-90), distance between the slots (between 3w-6w) and nanoparticle loading (between 0-2 % ) for the cases with and without PCM-PB zone. Phase tran-sition and heat transfer dynamics are influenced by the presence of magnetic field and varying its am-plitude/inclination. Complete phase change time (TP) is reduced by about 15 % and 11.7 % for pure liquid and nanoliquid when varying Ha from 0 to 10. Inclination of gamma = 0 provides the fastest phase transi-tion dynamics. Spatial average Nusselt number (Nu) rises by about 13.5 % by using impinging system with PCM+nanoliquid at the highest Ha as compared to system using only pure liquid. Phase transi-tion becomes slower for higher distance values between the slots while the average Nu rises by about 48.8 % . As the reference case of system using pure liquid without magnetic filed and without PCM are used, up to 84.88 % rise of average Nu is achieved by using PCM+nanoliquid under magnetic field at the highest strength. Dynamic fit for the thermal performance of the impinging system installed with PCM+nanoliquid under magnetic field with system identification is obtained.(c) 2022 Elsevier Ltd. All rights reserved.
Keywords: Multiple jet impingement; Magnetic field; Phase change dynamics; Finite element method; Hybrid nanofluid; System identification